A Sharp Break: Childs, Wellhausen, and Theo-referentiality - Cornell, Collin (Harvard theological review, 2019)
Julius Wellhausen proposed a "sharp break" between ancient Israelite religion and early Judaism: for him, the eighth-century prophets were the "spiritual destroyers of old Israel" and the forerunners of early Judaism. The biblical theologian Brevard Childs rejected Wellhausen's reconstruction and insisted instead that "very strong theological continuity" characterized the development of Israelite religion from its outset. Numerous contemporary theological interpreters share Childs's perspective. However, a "Wellhausen renaissance" is currently underway in the study of Israelite religion and early Judaism. This situation poses an unresolved challenge for theological interpretation, at least of the kind that Childs advocated. The present article addresses this dilemma. It first inventories Childs's reasons for opposing Wellhausen's sharp break, which emerge from Childs's vision for scriptural "theo- referentiality." Secondly, it tests whether Childs's theological insights, the very same that led to his repudiation of Wellhausen, might accommodate Wellhausen's historical claim. The final result is to set Wellhausen and Childs, historical reconstruction and theological interpretation, in a noncompetitive relationship.